Pemodelan Regresi Panel Spasial Pengaruh Kebijakan Desentralisasi Fiskal Terhadap Ketimpangan Pendapatan Antarkabupaten/kota di Provinsi Papua Tahun 2015-2020 - Reyhan Gesang Almuazam; Timbang Sirait (Seminar Nasional Official Statistics, 2022)
Differences in characteristics and resources between regions lead to income inequality. In order to achieve equitable region’s income, the Indonesian government implements a policy of fiscal decentralization. Papua Province is an area with high inter-regional inequality because the Papua’s Williamson Index value is above 0.8. Therefore, this study aims to find out the general description of income inequality between regions in Papua Province and analyze the effect of fiscal decentralization on income inequality between regions in Papua. The analytical method used in this research is spatial panel regression with the selected model Spatial Error Model Random Effect (SEM-RE). The results showed that the highest inequality occurred in Mimika and areas with high income inequality clustered around Mimika. Production agglomeration and HDI have a significant effect on income inequality. Meanwhile, the degree of fiscal independence, balancing funds, and the length of the road have no significant effect on income inequality. Income inequality of an area is also influenced by other variables outside the model from its neighbors.